Improvement of position and orientation of Unmanned Arial Vehicle (UAV) with INS/ GPS - Appala Raju, V; Vasundhara, P; ChandraKanth Reddy, V; Sai Aiswarya, A (International Journal of Engineering and Technology, 2018)
This paper deals with the methods performing state estimation .that is position and orientation of Unmanned Arial Vehicle (UAV) using GPS, gyro, accelerometers and magnetometer sensors. Various methods are designed for position and orientation measurements of UAV. In this paper we proposed extended kalman filter based inertial navigation system using quaternions and 3D magnetometer. Initially we load UAV truth data from a file ,generate noisy UAV sensor measurements and perform UAV state estimation and display UAV state estimate results with proposed method compares with previously exited method extendedÂ kalman filter based altitude and heading reference system using quaternion and 3D magnetometer simulation .Results shows that EKF-INS method gives better position and orientation of UAV.Â Â